E-LEARNING RESOURCES REQUIREMENTS STANDARDIZATION ACCORDING TO LEARNERS’ INDIVIDUAL NEEDS AND PREFERENCES - Michael V. Levin; Sergey E. Sosenushkin (Открытое образование (Москва), 2016)
The article considers the information models of e-learning resources requirements description and of the learners’ personal needs and preferences description. It presents the framework and the interconnections between the national and international e-learning content accessibility standards for different groups of users, including the ones with physical impairments.